Spontaneous hematuria after caesarean section: a case report and review of literature - Mohapatra, Ipsita; Samantaray, Subha Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Hematuria occurring postoperatively is typically associated with urinary tract infection, renal pathology, or surgical trauma. However, delayed-onset hematuria following caesarean section (CS) is uncommon and may point toward less frequently encountered etiologies directly or indirectly related to the surgical procedure. A patient presented with spontaneous gross hematuria on the 29th day after an uncomplicated CS. She had no fever, flank pain, or urinary symptoms. Preliminary investigations ruled out infection and renal pathology. Advanced imaging and cystoscopic evaluation were conducted to explore structural or vascular causes. Potential etiologies identified included retroperitoneal hematoma, vesicouterine fistula, and occult bladder injury. Diagnostic evaluation was challenged by the delayed timeline and non-specific presentation. Imaging techniques such as CT/MRI, cystoscopy, and dye tests proved critical in delineating the source. Spontaneous hematuria in the late postoperative period following CS is rare but warrants systematic evaluation to identify overlooked surgical or anatomical causes. Early diagnosis and targeted intervention are crucial to prevent long-term morbidity.